2002
DOI: 10.1016/s0165-5728(02)00143-1
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory signals increase Fas ligand expression by inner ear cells

Abstract: There is considerable evidence that hearing and vestibular function can be influenced by immune processes. The inner ear has evolved mechanisms, such as the blood-labyrinthine barrier that limit immune responses and autoimmune processes to reduce the potential for damage to cochlear cells. Recently, expression of Fas ligand (FasL) in some non-lymphoid tissue, as in the anterior chamber of the eye, has been hypothesized to play a role in protection of sensitive organs from activated T-cells. We show that under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
1
19
0
2
Order By: Relevance
“…Moreover, there was no increase in FasL transcripts and/or mRNA stability in the OC after IFN-Á stimulation. This result suggests that the increases in FasL that we previously observed on cochlear cells exposed to inflammatory stimulation [Bodmer et al, 2002] are not related to changes in gene transcription. It further suggests the possible presence of preformed FasL in normal cochlear cells, protein that is sequestered from FACS and standard cytochemical analysis.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Moreover, there was no increase in FasL transcripts and/or mRNA stability in the OC after IFN-Á stimulation. This result suggests that the increases in FasL that we previously observed on cochlear cells exposed to inflammatory stimulation [Bodmer et al, 2002] are not related to changes in gene transcription. It further suggests the possible presence of preformed FasL in normal cochlear cells, protein that is sequestered from FACS and standard cytochemical analysis.…”
Section: Discussionsupporting
confidence: 62%
“…In our previous study [Bodmer et al, 2002], FasL was observed on supporting cells in the OC of sections from animals undergoing a cochlear secondary immune response. No labeling was observed in hair cells.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The central nervous system, and the inner ear by extension, were originally thought to be immunoprivileged sites due to the presence of the blood-brain and the blood-labyrinthine barriers, respectively [Bodmer et al, 2002]. In 1958, Lehnhardt was the first to contradict the 'immunoprivileged site' theory about the inner ear.…”
Section: Introductionmentioning
confidence: 99%